Pelatihan Public Speaking Bagi Organisasi Dakwah Perempuan - Nur’aeni, Siti; Fauzia Hakim, Alfi; Fauzi Rahman, Mufti; Fauzan Albuchori, Ralvi; Komara Saputra, Deden (E-Coops-Day, 2025)
This Community Service Program (PKM) aims to improve the public speaking skills of PC Pemudi Persatuan Islam Rancaekek members. The training is designed to build confidence in public speaking, deliver messages clearly, and enhance communication skills within the organization. With strong speaking abilities, members are expected to be more confident in delivering dakwah and actively participating in organizational activities. The program uses the Participatory Rural Appraisal (PRA) approach, which actively involves participants in the learning process. They are introduced to public speaking techniques, trained in effective speech delivery, and given opportunities to practice their skills in various situations. The training is conducted interactively to ensure participants can develop their abilities directly. The results show an improvement in participants' public speaking skills, both in message delivery and audience interaction. Additionally, the training helps create a more communicative organizational environment. Evaluations are conducted to ensure the program continues to develop and provide lasting benefits for members of women's dakwah organizations.